2020
DOI: 10.1186/s13046-020-01552-8
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the transcriptional regulatory networks of promoter-associated noncoding RNAs in development and cancer

Abstract: In-depth analysis of global RNA sequencing has enabled a comprehensive overview of cellular transcriptomes and revealed the pervasive transcription of divergent RNAs from promoter regions across eukaryotic genomes. These studies disclosed that genomes encode a vast repertoire of RNAs beyond the well-known protein-coding messenger RNAs. Furthermore, they have provided novel insights into the regulation of eukaryotic epigenomes, and transcriptomes, including the identification of novel classes of noncoding trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 64 publications
3
21
0
Order By: Relevance
“…These are cis-acting elements which regulate the expression of their neighbouring genes. The PALPs have recently emerged as an important epigenetic regulator of genes involved in a variety of diseases [ 59 ]. Myoparr is a promoter associated lncRNAs, which is transcribed from the promoter region of human and mouse myogenin gene.…”
Section: Introductionmentioning
confidence: 99%
“…These are cis-acting elements which regulate the expression of their neighbouring genes. The PALPs have recently emerged as an important epigenetic regulator of genes involved in a variety of diseases [ 59 ]. Myoparr is a promoter associated lncRNAs, which is transcribed from the promoter region of human and mouse myogenin gene.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of gene sequencing, numerous lncRNAs have been identi ed that are dysregulated in the human genome [40]. A growing body of evidence has indicated that the dysregulated lncRNAs are closely related with the genesis and progression of EOC and involved in the control of nearly all types of tumorigenic behavior [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of gene sequencing, numerous lncRNAs have been identi ed that are dysregulated in the human genome [40]. A growing body of evidence has indicated that the dysregulated lncRNAs are closely related with the genesis and progression of EOC and are involved in the control of nearly all types of tumorigenic behavior [41][42][43].…”
Section: Discussionmentioning
confidence: 99%